Answer:
the slope is 1
Step-by-step explanation:
Answer:heyya
Step-by-step explanation:
<h3>
coefficient means the number before the variables...the coefficient of y is 5..i dont know whether that is X or multiplication sign..if it is the variable X raise to the power 2 then the coefficient of X raise to the power 2 is 4..</h3><h3>hope it helps</h3>
There are two numbers whose sum is 64. The larger number subtracted from 4 times the smaller number gives 31. Then the numbers are 45 and 19
<h3><u>
Solution:</u></h3>
Given that, There are two numbers whose sum is 64.
Let the number be a and b in which a is bigger.
Then, a + b = 64 ------ eqn (1)
The larger number subtracted from 4 times the smaller number gives 31.
4 x b – a = 31
4b – a = 31 ----- eqn (2)
We have to find the numbers.
So, from eqn (2)
a = 4b – 31
Subatitute a in (1)
4b – 31 + b = 64
On solving we get
5b = 64 + 31
5b = 95
b = 19
So, b = 19, then eqn 1
a + 19 = 64
On simplification,
a = 64 – 19
a = 45
Hence, the two numbers are 45 and 19
To find the total number of text messages sent, you will use the stem-n-leaf plot to create a data set of all the numbers of texts sent.
To read a stem-n-leaf plot you will use the number on the left as the tens place and each number to the right of it creates a new number in the data set.
See the key for help!
Here is the list of the all the data:
0, 0, 7, 9, 10, 10, 15, 20, 23, 32
To find the total number of text messages sent, add these together.
The answer is 126 text messages.
Answer:
Step-by-step explanation:
Polynomial f(x) has the following conditions: zeros of -4 (multiplicity 3), 1 (multiplicity 1), and with f(0) = 320.
The first part zeros of -4 means (x+4) and multiplicity 3 means (x+4)^3.
The second part zeros of 1 means (x-1) and multiplicity 1 means (x-1).
The third part f(0) = 320 means substituting x=0 into (x+4)^3*(x-1)*k =320
(0+4)^3*(0-1)*k = 320
-64k = 320
k = -5
Combining all three conditions, f(x)
= -5(x+4)^3*(x-1)
= -5(x^3 + 3*4*x^2 + 3*4*4*x + 4^3)(x-1)
= -5(x^4 + 12x^3 + 48x^2 + 64x - x^3 - 12x^2 - 48x - 64)
= -5(x^4 + 11x^3 + 36x^2 + 16x -64)
= -5x^3 -55x^3 - 180x^2 - 80x + 320